Election and democracy reflections on the Asian experiences 2009. - Minjuhwa Undong Kiny?om Sa?ophoe. (Seoul, Korea Korea Democracy Foundation, 2009)
"This nine country reports highlight ... variables that shape and direct elections i.e. the socio-political background of the election; the election law and its adherence; the manner and tendency in which state resources and media were utilized; the atmosphere and tendency in which the pre-election monitoring and observation activities were operated; and, the analysis of election results and its implications for future democracies and social change."-- Introduction p. xi.
Keywords: Democracy -- History. -- Asia; Democracy -- Politics and government -- 21st century. -- Asia; Democracy -- Sociological aspects -- 21st century. -- Asia; Elections -- History. -- Asia; Elections -- Politics and government -- 21st century. -- Asia; Elections -- Sociological aspects -- 21st century. -- Asia